2021
DOI: 10.1136/jclinpath-2021-207776
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of the COVID-19 pandemic on UK HbA1c testing: implications for diabetes management and diagnosis

Abstract: AimsThe COVID-19 pandemic, and the focus on mitigating its effects, has disrupted diabetes healthcare services worldwide. We aimed to quantify the effect of the pandemic on diabetes diagnosis/management, using glycated haemoglobin (HbA1c) as surrogate, across six UK centres.MethodsUsing routinely collected laboratory data, we estimated the number of missed HbA1c tests for ‘diagnostic’/‘screening’/‘management’ purposes during the COVID-19 impact period (CIP; 23 March 2020 to 30 September 2020). We examined pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…Remote monitoring systems proved to be feasible and were supported by the current clinical guidelines [ 3 ]. However, the study results might represent a considerable burden of unmet need, validating the results of other studies [ 2 , 8 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Remote monitoring systems proved to be feasible and were supported by the current clinical guidelines [ 3 ]. However, the study results might represent a considerable burden of unmet need, validating the results of other studies [ 2 , 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have identified that missed hemoglobin A 1c (HbA 1c ) monitoring appointments is associated with higher HbA 1c [ 6 , 7 ]. A recent study showed a 40% reduction in HbA 1c testing during the first year of the COVID-19 pandemic compared to the preceding year [ 8 ]. It is well established that impaired glycemic control is associated with the increased risk of micro- and macrovascular complications [ 8 , 9 ], indicating the benefit to people with T2DM having regular HbA 1c monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are particularly pertinent as we come to appreciate the consequences of the COVID-19 pandemic on the way that routine care for people with diabetes is delivered. In this regard, we recently reported a fall in volume of HbA1c tests following the first UK lockdown in March 2020 [ 33 ]. Specifically, by September 2020, there were as many as 1.41 million missed/delayed diabetes monitoring tests, including an estimated 0.51 million in people with suboptimal blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that these factors be considered when planning psychosocial interventions and behavior change messaging to support people with diabetes, in relation to the multiple challenges that they face, particularly given the impact of the COVID-19 pandemic on routine care for people with diabetes in the UK and elsewhere [ 4 ].…”
mentioning
confidence: 99%
“…We conducted an online survey of people with diabetes, who had agreed to be involved through the research for the future (RfTF) project, in relation to their lived experience of the condition [4]. PHQ-9 (depression) [5], Diabetes Distress Screening Scale (DDSS) [6] and EQ5D5L QOL [7] questionnaires were completed by 130 people with diabetes and their clinical records were also examined.…”
mentioning
confidence: 99%